Antioxidative potential and compositional variation among Origanum vulgare L. collected from different districts of Kumaun Himalayas, Uttarakhand. Issue 2 (3rd March 2020) - Bhatt, Sunita; Tewari, Geeta; Pande, Chitra; Punetha, Deepshekha; Prakash, Om
ABSTRACT: The present study investigated the compositional variation and antioxidant potential of Origanum vulgare L. (subsp. vulgare ) collected from three districts of Uttarakhand, India. The essential oil composition was analyzed by GC and GC/MS, and the antioxidant potential was evaluated using 2, 2ʹ-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, ferric reducing antioxidant power (FRAP) activity and Fe 2+ -ferrozine test system for iron-chelating activity methods. The analysis allowed the identification of 22–36 compounds representing 87.84–92.95% of the total essential oil. Samples S1 and S2 contained a high amount of sesquiterpene hydrocarbons (26.37–47.25%), while sample S3 was rich in oxygenated monoterpenes (70.21%). The major component was ( E) -caryophyllene in S1 and S2 samples (15.40–26.41%) and thymol (60.3%) in S3 sample. The S3 sample collected from the lowest altitude showed the highest oil yield and antioxidant activity.